1999
DOI: 10.1007/3-540-47954-6_1
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling for Parallel Supercomputing: A Historical Perspective of Achievable Utilization

Abstract: Abstract.The NAS facility has operated parallel supercomputers for the past 11 years, including the Intel iPSC/860, Intel Paragon, Thinking Machines CM-5, IBM SP-2, and Cray Origin 2000. Across this wide variety of machine architectures, across a span of 10 years, across a large number of different users, and through thousands of minor configuration and policy changes, the utilization of these machines shows three general trends: (1) scheduling using a naive FCFS first-fit policy results in 40-60% utilization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 5 publications
2
46
0
1
Order By: Relevance
“…As observed in various previous studies [16], the StartUp policy has the lowest utilizations, from 20% to 30%-in line to traditional provisioning policies that only look at peak workloads. As in previous studies of utilization [32], ODS, the commonly used policy in current data centers, achieves only a moderate utilization of 65% to 80%. Our portfolio scheduler combines consistently low job slowdown and wait time, with low cost (through high utilization).…”
Section: Results Of Synthetic Workloadsmentioning
confidence: 55%
“…As observed in various previous studies [16], the StartUp policy has the lowest utilizations, from 20% to 30%-in line to traditional provisioning policies that only look at peak workloads. As in previous studies of utilization [32], ODS, the commonly used policy in current data centers, achieves only a moderate utilization of 65% to 80%. Our portfolio scheduler combines consistently low job slowdown and wait time, with low cost (through high utilization).…”
Section: Results Of Synthetic Workloadsmentioning
confidence: 55%
“…This suggests that at any given moment some fraction of the usable nodes will be sitting idle, even when jobs are waiting to run in the queue. In fact, studies have shown that FCFS only manages to achieve around 40-60% node utilization, while EASY does somewhat better at around 70% node utilization [32].…”
Section: Batch Schedulingmentioning
confidence: 99%
“…This problem is solved by backfilling algorithms, which allow small jobs from the back of the queue to execute before larger jobs that arrived earlier, thus utilizing the idle processors, while the latter are waiting for enough processors to be freed [15]. Backfilling is known to greatly increase user satisfaction since small jobs tend to get through faster, while bypassing large ones [11,2]. Note that backfilling algorithms require the jobs' runtimes to be known in advance.…”
Section: Scheduling With Backfillingmentioning
confidence: 99%
“…Dynamic backfilling allows the scheduler to overrule a previous reservation if introducing a slight delay will improve utilization considerably [11]. Talby and Feitelson presented slack based backfilling, an enhanced backfill scheduler that supports priorities [26].…”
Section: Scheduling With Backfillingmentioning
confidence: 99%